PRAKTIK UTANG PIUTANG SEMBAKO DIBAYAR JASA KERJA PERTANIAN DALAM PERSPEKTIF HUKUM ISLAM - Novi Safitri; Hatoli Hatoli; Zarul Arifin (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
Basic food receivables are a practice that occurs in Kalimantan Village, Paloh District, Sambas Regency. This practice occurs when the debtor asks for help from the shop to owe the groceries. Regarding the payment through agricultural work on the shop owner's agricultural land and the calculation of the payment of the food receivables payable is calculated after the debtor has finished working on the shop owner's farm. So that previously it was not known how much debt was incurred by the debt recipient. From the problems regarding this debt and credit, then the formulation of the problem can be taken as follows; first, how is the practice of basic food receivables paid for agricultural work services in Kalimantan Village, Paloh District, Sambas Regency. Second, how is the review of Islamic law on the practice of basic food receivables paid for agricultural work services. The method used in this research is descriptive method using a sociological normative approach, the type of research used is qualitative, the data collection techniques used are observation techniques, interview techniques, and documentation. From the research results show, the practice of debt and credit paid by agricultural work services has been in line with the pillars and terms of the Qard contract. However, it is not valid according to Islamic law because the debtor (muqtarid) does not know from the start and does not know exactly how much in total he owes. And it only became known after he finished working on the farm owned by the party who gave the debt.